2017
DOI: 10.1037/cfp0000079
|View full text |Cite
|
Sign up to set email alerts
|

A dyadic perspective on PTSD symptoms’ associations with couple functioning and parenting stress in first-time parents.

Abstract: Posttraumatic stress disorder (PTSD) symptoms are associated with disruptions in both couple functioning and parenting, and limited research suggests that, among military couples, perceptions of couple functioning and parenting stress are a function of both one’s own and one’s partner’s mental health symptoms. However, this work has not been generalized to civilian couples, and little is known about the associations between PTSD symptoms and family adjustment in specific family developmental contexts. We exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 56 publications
3
10
0
Order By: Relevance
“…The opposite was true when survivors reported high partner support. Finally, Fredman, Le, Marshall, Brick, and Feinberg (2017) found that partner effects of PTSD symptoms on couple functioning were unexpectedly stronger in men than in women when men received a couple-based coparenting intervention. Greater focus on the influences of sex, gender, and sexual orientation is needed to further our understanding of these issues.…”
Section: Contextual Moderatorsmentioning
confidence: 92%
“…The opposite was true when survivors reported high partner support. Finally, Fredman, Le, Marshall, Brick, and Feinberg (2017) found that partner effects of PTSD symptoms on couple functioning were unexpectedly stronger in men than in women when men received a couple-based coparenting intervention. Greater focus on the influences of sex, gender, and sexual orientation is needed to further our understanding of these issues.…”
Section: Contextual Moderatorsmentioning
confidence: 92%
“…PTSD can negatively influence relationships with friends or significant others (Fredman et al, 2017;McLean, Rosenbach, Capaldi, & Foa, 2013). PTSD symptoms may impair social skills or lead to avoidance of social situations that individuals fear may trigger memories of past trauma.…”
Section: Effects Of Net On Couple and Peer Relationshipsmentioning
confidence: 99%
“…One study found that, among adolescent girls exposed to sexual assault and violence, higher PTSD symptom severity was associated with lower social functioning (McLean et al., ). In addition, ample research supports a negative association between PTSD and couple relationship quality (e.g., Fredman et al., ). One study found that individual PTSD symptoms were associated both with their own perceptions of couple functioning as well as their partner's perception of couple functioning (Fredman et al., ).…”
Section: Interpersonal Implications Of Traumatic Stress and Net Treatmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysphoric arousal symptoms were also strongly associated with parental conflict among trauma-exposed adolescents (Sumner et al, 2014). In postpartum and parenting women, total PTSD symptoms have been linked to parenting stress (Ammerman et al, 2012;Chemtob et al, 2013;Fredman et al, 2017;Samuelson et al, 2017;Wilson et al, 2017); aggression in couple relationships (Fredman et al, 2017;Marshall et al, 2019); and IPV (Sumner et al, 2012). Another relevant health correlate for new mothers is contraceptive use.…”
Section: Introductionmentioning
confidence: 99%